Incorporation, adaptation and rejection of obstetric practices during the implementation of the “Adequate Childbirth Program” in Brazilian private hospitals: a qualitative study - Débora Cecília Chaves de Oliveira; Maysa Luduvice Gomes; Andreza Rodrigues; Thamires Soares; Lucia Regina de Azevedo Nicida; Jacqueline Alves Torres; Elyne Montenegro Engstrom (Reproductive Health, 2024)
Abstract Background The “Adequate Childbirth Program” (PPA) is a quality improvement project that aims to reduce the high rates of unnecessary cesarean section in Brazilian private hospitals. This study aimed to analyze labor and childbirth care practices after the first phase of PPA implementation. Method This study uses a qualitative approach. Eight hospitals were selected. At each hospital, during the period of 5 (five) days, from July to October 2017, the research team conducted face to face interviews with doctors (n = 21) and nurses (n = 28), using semi-structured scripts. For the selection of professionals, the Snowball technique was used. The interviews were transcribed, and the data submitted to Thematic Content Analysis, using the MaxQda software. Results The three analytical dimensions of the process of change in the care model: (1) Incorporation of care practices: understood as the practices that have been included since PPA implementation; (2) Adaptation of care practices: understood as practices carried out prior to PPA implementation, but which underwent modifications with the implementation of the project; (3) Rejection of care practices: understood as those practices that were abandoned or questioned whether or not they should be carried out by hospital professionals. Conclusions After the PPA, changes were made in hospitals and in the way, women were treated. Birth planning, prenatal hospital visits led by experts (for expecting mothers and their families), diet during labor, pharmacological analgesia for vaginal delivery, skin-to-skin contact, and breastfeeding in the first hour of life are all included. To better monitor labor and vaginal birth and to reduce CS without a clinical justification, hospitals adjusted their present practices. Finally, the professionals rejected the Kristeller maneuver since research has demonstrated that using it’s harmful.